Excess burden of age-associated comorbidities among people living with HIV in British Columbia, Canada: a population-based cohort study. Issue 1 (8th January 2021) - Nanditha, Ni Gusti Ayu; Paiero, Adrianna; Tafessu, Hiwot M; St-Jean, Martin; McLinden, Taylor; Justice, Amy C; Kopec, Jacek; Montaner, Julio S G; Hogg, Robert S; Lima, Viviane D
Abstract : Objectives: As people living with HIV (PLWH) live longer, morbidity and mortality from non-AIDS comorbidities have emerged as major concerns. Our objective was to compare prevalence trends and age at diagnosis of nine chronic age-associated comorbidities between individuals living with and without HIV. Design and setting: This population-based cohort study used longitudinal cohort data from all diagnosed antiretroviral-treated PLWH and 1:4 age-sex-matched HIV-negative individuals in British Columbia, Canada. Participants: The study included 8031 antiretroviral-treated PLWH and 32 124 HIV-negative controls (median age 40 years, 82% men). Eligible participants were ≥19 years old and followed for ≥1 year during 2000 to 2012. Primary and secondary outcome measures: The presence of non-AIDS-defining cancers, diabetes, osteoarthritis, hypertension, Alzheimer's and/or non-HIV-related dementia, cardiovascular, kidney, liver and lung diseases were identified from provincial administrative databases. Beta regression assessed annual age-sex-standardised prevalence trends and Kruskal-Wallis tests compared the age at diagnosis of comorbidities stratified by rate of healthcare encounters. Results: Across study period, the prevalence of all chronic age-associated comorbidities, except hypertension, were higher among PLWH compared with their community-based HIV-negative counterparts; as much as 10 times higher for liver diseases (25.3% vs 2.1%, p value<0.0001). On stratification by healthcare encounter rates, PLWH experienced most chronic age-associated significantly earlier than HIV-negative controls, as early as 21 years earlier for Alzheimer's and/or dementia. Conclusions: PLWH experienced higher prevalence and earlier age at diagnosis of non-AIDS comorbidities than their HIV-negative controls. These results stress the need for optimised screening for comorbidities at earlier ages among PLWH, and a comprehensive HIV care model that integrates prevention and treatment of chronic age-associated conditions. Additionally, the robust methodology developed in this study, which addresses concerns on the use of administrative health data to measure prevalence and incidence, is reproducible to other settings.